McKeown esophagectomy for a thoracic esophageal carcinoma patient who has a history of definitive chemoradiotherapy for esophageal carcinoma and total pharyngolaryngectomy for hypopharyngeal cancer - Kotaro Sugawara; Takashi Fukuda; Yutaka Kishimoto; Daiji Oka; Satoru Shirakura; Hiroaki Kanda; Yoshiyuki Kawashima (World Journal of Surgical Oncology, 2023)
Abstract A 64-year-old man, who had previously undergone definitive chemoradiotherapy (dCRT) and endoscopic resections for metachronous multiple esophageal squamous cell carcinoma (ESCC) and had also received total pharyngolaryngectomy (TPL) for hypopharyngeal cancer, was diagnosed with ESCC in the middle thoracic esophagus (cT3N0M0). Thoracoscopic McKeown esophagectomy was performed for the patient. Although the tumor was tightly adherent to the thoracic duct and both main bronchi, they were successfully mobilized. In order to maintain the blood supply to the trachea, we preserved the bilateral bronchial arteries and avoided prophylactic upper mediastinal lymph node dissection. Cervical end-to-side anastomosis between the jejunum and a gastric conduit was performed. Minor pneumothorax was managed conservatively, and the patient was discharged 44 days after the surgery. Overall, thoracoscopic McKeown esophagectomy was safely performed in a patient with a history of TPL and dCRT. Surgeons should be very careful to prevent tracheobronchial ischemia by optimizing the extent of lymph node dissection.